Kepastian Kewenangan Penegakan Hukum Terhadap Advokat yang Obstraction Of Justice Tindak Pidana Korupsi di Indonesia - Iswandy Rani Saputra (Jurnal Restorative Justice, 2021)
The purpose of this study is to determine the application of law to lawyers who obstruct and obstruct the course of the investigation process in corruption cases and to find out the limitations of Advocate immunity rights contained in Law number 18 of 2003 concerning Advocates in carrying out their profession as a law enforcer. This study uses a case-related approach from the cases studied, both from talks in the media and from the facts of the trial and a normative juridical approach. The results of this study indicate that there are two criminal rules governing lawyers who obstruct and obstruct the course of the investigation process in corruption cases, namely in article 216 of the Criminal Code and Article 21 of the Corruption Crime Law, investigations, investigations and charges made by the KPK in cases. Advocates who obstruct and obstruct the proceeding of the examination should be null and void if based on statutory regulations and jurisprudence of the Supreme Court's ruling on general criminal charges. thus, advocates have the right to immunity as stated in article 16 of the Advocate Law.